Primary Cutaneous Actinomycosis along with the Surgical Scar on the Hand - Reza M. Robati; Nasim Niknezhad; Farahnaz Bidari-Zerehpoush; Nakisa Niknezhad (Case Reports in Infectious Diseases)
Primary cutaneous actinomycosis is a rare clinical form with variable presentation. The tumoral presentation of actinomycosis as pseudocarcinomatous or sarcomatous masses is completely rare. The management of cutaneous actinomycosis needs proper antibiotic treatment and surgical resection would not be adequate alone. Herein, we report a case of primary cutaneous actinomycosis on the dorsal surface of the hand as draining and infiltrated lesions along with the scar of previous tumor excision that had not received proper antibiotics after the surgery.